APLIKASI MOBILE ALUMNI CENTER (STUDI KASUS DI INSTITUT SAINS & TEKNOLOGI AKPRIND) - Kartika Indayani; Catur Iswahyudi; Erfanti Fatkhiyah (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Alumni Database Institute of Science and Technology AKPRIND Yogyakarta needs an update, so as to create an active communication between the alumni and the institution. Communication with the Alumni should not be interrupted for granted. Therefore, this study build mobile applications that help process data collection Institute of Science and Technology Alumni AKPRIND Yogyakarta is complete and can be updated easily anytime, communications to connect with alumni through a communication forum and were able to trace the Alamuni with features tracer study. Applications built based on Android and the web client server model. The mobile apps are used for alumni and web applications for the administrator. Mobile application consists of a login, update your bio, gallery alumni tracer study questionnaire and forum alumni. While the web application consists of alumni data processing and reporting as well as to control the alumni forum. Applications can be mounted on various variants of android starting from version Froyo or later. Data communication in mobile applications both storage and retrieval of data using an external database system MySQL with support for PHP Programming Language and JSON protocol.